Jasa ekosistem persawahan sebagai pengelolaan keberlanjutan - Husaeri, Husaeri (Maliki Interdisciplinary Journal, 2024)
Rice field ecosystems are considered relatively unstable due to the majority adopting monoculture farming systems, leading to low ecosystem stability caused by the lack of plant diversity. To enhance the stability of rice field ecosystems, a more complex farming system is needed to increase organism diversity with various roles and functions within the ecosystem. Rice field ecosystems consist of abiotic and biotic components, including rice plants, shrubs, and various other organisms. The importance of ecosystem services from rice fields is reflected in food provision, water filtration, habitat for biodiversity, flood regulation, carbon storage, and tourism attraction. Sustainable management of rice fields requires attention to abiotic, biotic, and human cultural components, along with the application of appropriate technology to ensure optimal rice production without harming the environment. Common issues in rice field ecosystems include soil pollution, pest attacks, weather changes, fertilizer and pesticide use, genetic engineering, land narrowing, and human activities’ impacts. Sustainable management efforts by farmers using creative innovation and environmentally friendly technology are key to maintaining the sustainability of rice field ecosystems.